Language Norms: What and where are they? - Ask Zaar, Balder Edmund (Public Journal of Semiotics, 2022)
The notion of a language norm is far from clear. Lacking a conclusive explication, one may wonder what language studies are actually studying. Is it the experience of speakers? Is it their brains? Is it their behavior? Is it the product of expert intuitions? Even within linguistics the views seem scattered on this point, and no consensus has been reached on what the object of study in linguistics is supposed to be. The ontology of language norms is thus of high relevance, not only philosophically, but for the empirical implications of any potential ontological claim. In a question: what are we studying when we are studying language norms? This paper is thus an effort to, primarily with the help of Husserlian phenomenology, discuss language norms and their location in order to answer this question as well as to obviate or at least mitigate some of the concerning trends found in recent discussions on language norms.